THE DEVELOPMENT OF CARBOHYDRATE E-MODULE İNTEGRATED BY KKNI TASKS DURING THE COVID-1 PANDEMIC - Wan Azura; Albinus Silalahi; Moondra Zubir (Universitas Muhammadiyah Semarang, 2021)
The transformation of education during the COVID-19 pandemic requires that the elements of education be proficient in using technology according to the online learning system so that it has a positive impact on the demands of the digital era in the future. The research is R & D (Research & Development) oriented with the application of the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) but in this study it only went through three ADDIE stages. E-module development based on syllabus analysis and RPS development refers to KKNI. for biochemistry courses, especially on carbohydrates. E-module validation is assessed by expert validators based on BSNP standards (content feasibility, language eligibility, and presentation). The data collection instrument in this study used a questionnaire which was presented in google form. Based on the validation results of the development of integrated carbohydrate e-module, KKNI tasks during the COVID-19 pandemic with content feasibility, language feasibility, and presentation feasibility scores, respectively 3.61, 3.53, and 3.58 so that the e-module that has been developed is very feasible to use as a learning media. e-module of carbohydrate based KKNI tasks had implemented as a learning media in the future.Keywords: e-module, carbohydrate, KKNI, COVID-19, learning media